Engineering the production of conjugated fatty acids in Arabidopsis thaliana leaves. Issue 8 (15th March 2017) - Yurchenko, Olga; Shockey, Jay M.; Gidda, Satinder K.; Silver, Maxwell I.; Chapman, Kent D.; Mullen, Robert T.; Dyer, John M.
Summary: The seeds of many nondomesticated plant species synthesize oils containing high amounts of a single unusual fatty acid, many of which have potential usage in industry. Despite the identification of enzymes for unusual oxidized fatty acid synthesis, the production of these fatty acids in engineered seeds remains low and is often hampered by their inefficient exclusion from phospholipids. Recent studies have established the feasibility of increasing triacylglycerol content in plant leaves, which provides a novel approach for increasing energy density of biomass crops. Here, we determined whether the fatty acid composition of leaf oil could be engineered to accumulate unusual fatty acids. Eleostearic acid (ESA) is a conjugated fatty acid produced in seeds of the tung tree ( Vernicia fordii ) and has both industrial and nutritional end‐uses. Arabidopsis thaliana lines with elevated leaf oil were first generated by transforming wild‐type, cgi‐58 or pxa1 mutants (the latter two of which contain mutations disrupting fatty acid breakdown) with the diacylglycerol acyltransferases ( DGAT1 or DGAT2 ) and/or oleosin genes from tung. High‐leaf‐oil plant lines were then transformed with tung FADX, which encodes the fatty acid desaturase/conjugase responsible for ESA synthesis. Analysis of lipids in leaves revealed that ESA was efficiently excluded from phospholipids, and co‐expression of tung FADX and DGAT2 promoted a synergistic increase in leaf oil content and ESA accumulation. Taken together, these results provide a new approach for increasing leaf oil content that is coupled with accumulation of unusual fatty acids. Implications for production of biofuels, bioproducts, and plant–pest interactions are discussed.